Strategies for Integrating Indigenous Knowledge in Primary Education and its Impacts on Sustainable Development and Inclusive Growth - Okeke Tobechukwu Ebele (Journal of Gender and Millennium Development Studies, 2024)
Background: Incorporating indigenous knowledge into formal education systems has gained global attention as a means to promote cultural sustainability, environmental awareness, and inclusive development. However, in many regions like Nigeria, indigenous knowledge remains underutilized in primary education. Objective: This study aimed to explore strategies for integrating indigenous knowledge into primary education in Nigeria and examine its impact on sustainable development and inclusive growth. Method: A descriptive survey design was employed, involving 111 participants comprising primary school teachers, educational administrators, and indigenous community members across selected Local Government Areas (LGAs) in Nigeria. Data were collected using a structured questionnaire validated by experts and pilot-tested with 30 respondents, yielding a reliability coefficient of 0.74. Data analysis involved descriptive statistics and Chi-Square tests. Result: Findings revealed that integrating indigenous language in curriculum development and utilizing hands-on materials and experimentation significantly enhanced students’ cultural and environmental understanding. Furthermore, these strategies fostered empathy, encouraged multicultural awareness, and led to improved educational outcomes among students from diverse backgrounds. Conclusion: The integration of indigenous knowledge into primary education supports sustainable development goals by enriching student learning and promoting inclusive educational practices. Contribution: This research provides practical insights for curriculum planners, educators, and policymakers on embedding indigenous knowledge systems into early education to drive sustainable and inclusive societal progress.